Design of Grid-Connected Solar PV Power Plant in Riyadh Using PVsyst - Mubarak M. Alkahtani; Nor A. M. Kamari; Muhammad A. A. M. Zainuri; Fathy A. Syam (Energies)
Solar energy is a quick-producing source of energy in Saudi Arabia. Solar photovoltaic (PV) energy accounts for 0.5% of electricity output, with a total installed capacity of 9.425 GW and 9353 solar power plants of various types globally. Many solar power stations will be established on different sites in the coming years. The capacity of these stations reaches hundreds of megawatts. The primary aim of this study is to facilitate the strategic and systematic assessment of the solar energy resource potential that impacts both large and small-scale solar power projects in Saudi Arabia. This study describes in detail the analysis, simulation, and sizing of a 400 MW grid-connected solar project for the Riyadh, Saudi Arabia site using the PVSyst 8 software program. The software-generated trajectories primarily represent the performance of a PV system at a certain location. It provides data for the geographical position used by maps for component sizing, projecting the installation under extremely realistic conditions. The report further examines the system’s behavior with various tilt and orientation settings of the PV panel, which yields superior simulation results at equivalent latitudes for any practical sizing. Three types of PV modules with different sizes are used to design the solar plant. The main project was designed using 580 WP and was compared with 330 WP and 255 WP power modules. This study confirmed that high-power PV modules are more efficient than small modules.